Pheochromocytoma Presenting as Acute Heart Failure Leading to Cardiogenic Shock and Multiorgan Failure - Jochen Steppan; Julia Shields; Ralph Lebron (Case Reports in Medicine)
Pheochromocytoma is an endocrine tumor classically presenting with headache, paroxysmal hypertension, and palpitations. We discuss the case of a young male, presenting with acute heart failure and cardiogenic shock requiring stabilization with an intra-aortic balloon pump and a combination of ionotropes and vasopressors. Pheochromocytoma was diagnosed by CT scan, as well as urine and plasma metanephrines. After pretreatment with phenoxy-benzamine, the patient underwent adrenalectomy with subsequent cardiovascular stabilization and full recovery. Unfortunately, pheochromocytoma often remains undiagnosed. Given the ample diagnostic tools and good prognosis when treated suitably, the diagnosis should be entertained early in patients, presenting with unexplained cardiovascular compromise.